Optimal strategies for identifying kidney disease in diabetes : properties of screening tests, progression of renal dysfunction and impact of treatment – systematic review and modelling of progression and cost-effectiveness /: properties of screening tests, progression of renal dysfunction and impact of treatment – systematic review and modelling of progression and cost-effectiveness. (February 2014) - Farmer, A. J (Andrew J.)
No abstract available